CLASS OBSERVATIONS IN BENINESE TECHNICAL SCHOOLS AND LAURENT CANTET’S FILM ‘‘ENTRE LES MURS’’: AN INSTRUMENT FOR TEACHERS’ SELF- DEVELOPMENT AND TEACHER TRAINING. A CASE STUDY OF TECHNICAL SCHOOLS IN BENIN REPUBLIC - TEBA, Corneille Sourou (My University, 2017)
This article aims fundamentally at showing that through classroom observations a lot of disciplinary as well as pedagogical and methodological problems could be solved. This paper pairs up the results from both questionnaires and class room observations in technical schools with events from the film ‘‘ENTRE LES MURS’’. The results from the interviews is also taken into account to analyse with problem solving strategies in the film and the practices in different technical schools to see to what extent classroom observations, either self or done by other people, can help teacher to self-develop and become professionally competent for the good of both learners and teachers themselves. Field survey is used and the target population was teachers and students in technical schools in Benin.
Keywords: Classroom; observations; technical schools; self-development; teachers’ training